A Historical Perspective on Environmental Kuznets Curve - Ozcan, Burcu; Ozturk, Ilhan (Academic Press Ltd-Elsevier Science Ltd, 2019)
[Abstract Not Available]
Keywords: Economic-Growth; Ecological Footprint; Sustainable Development; Time-Series